Kierunki rozwoju rynku energii wiatrowej: Directions of development of wind energy sector - Niedziółka, Monika (Management and Administration Journal, 2021)
The renewable energy is developing very dynamically. Some actions taken in the area of this kind of energy is an effect of the energy policy pursued by countries and international organizations. It results from the diligence and care about the natural environment as well as from the need of energy safety in particular regions. From among different renewable energy sources the special attention is worth to be put to the wind energy. This is the sector where the most dynamic changes are being made. Significant changes are also made in the polish wind energy sector. Few years ago, in Poland were standing up first professional wind farms projects. Nowadays, this sector of energy is starting to play more and more relevant role. In 2010 wind energy became a dominant renewable energy source in Poland.